Pengaruh Ukuran Perusahaan, Stabilitas Keuangan, Tekanan Eksternal Terhadap Kecurangan Laporan Keuangan (Studi Kasus Pada Perusahaan Industri Barang Konsumsi Sub Sektor Makanan Dan Minuman Yang Terdaftar di BEI) - Yuliana Gultom; Tuti Meutia; Iqlima Azhar (LPPM Universitas Labuhanbatu, 2022)
The subject of this study is the company’s size, financial stability, and the influence of external factors on financial statement fraud. In this study, using quantitative methods. The population and research sample consisted of all food and beverage businesses listed on the IDX of the Indonesian Stock Exchange. Multiple linear regression on this study was used with the help of SPSS. This research the regression equation is: Y= 5,792 + 0,003X1 – 0,011X2 + 0,015X3. Firm size has a positive but not significant value of financial statement fraud, according to these findings stability one’s finances has negative but not significant value, and external pressure has a significant and positive impact value on financial statement fraud. Simultaneously company size, financial stability, and external pressure all have a significant impact on fraudulent financial statement. The lack of recent references and the most recent theories regarding firm size, financial stability, and external pressure are the study’s recommendations will focus on the variables and other factors that influence financial statement fraud so that business actors can achieve financial stability and avoid fraud. To avoid fraud pressure from outside.